Comparative Study of the Specific Activity of Carbon and Lignin Enterosorbents - Ismailova, M.G.; Nabiev, A.; Ismailova, P.L. (Хімія, фізика та технологія поверхні, 2010)
The technology of obtaining was designed and comparative tests of the medical enterosorbents, activated coal (AU-K) and lignin enterosorbents (LE) were carried out. AU-K possesses by mainly developed micro- and media-porous structure, lignin enterosorbent – by macro-porous structure. However, significant set of the oxygen-containing functional groups on LE surfaces conditions its high activity at the treatment of the lacto-dependent diarrhoea.